Association of Mean Platelet Volume with Diabetic Retinopathy in Type 2 Diabetes Mellitus (Ibrahim Cardiac Medical Journal, 2023)
Background & Objective: Diabetic retinopathy is a common microvascular complication of Type2 diabetes mellitus. As diabetes is a prothrombotic disease, it induces platelet hyperactivity resulting in increased mean platelet volume (MPV) which can be measured from complete blood count by haematology auto-analyzer. This study was undertaken to find the association of MPV with diabetic retinopathy in Type 2 diabetes mellitus (DM).Methods: The study was carried out in the Department of Medicine, Sylhet MAG Osmani Medical College & Hospital, Sylhet in collaboration with the Department of Pathology, Department of Endocrinology & Outpatient Department of Ophthalmology of the same hospital over a period of two years from March 2017 to February 2019. Type 2 diabetic patients (aged 30 years or more) attending at Inpatient and Outpatient Department of Medicine, Endocrinology & Outpatient Department of Ophthalmology were the target population. Based on predefined eligibility criteria, 63 Type2 diabetic patients 31 Type2 diabetic patients with diabetic retinopathy (DR) and 32 diabetic patients without DR were included in the study. To find the normal range of MPV of Bangladeshi population, 30 adult individuals without diabetes were also included. The mean of MPV of 30 adult healthy individuals + 2SD were taken as upper limit of normal range of MPV. Diagnosis of T2DM was based on "2017 ADA criteria for diagnosing DM". Diabetic retinopathy was defined as any vascular abnormality in retina due to DM.Result: Age and sex were almost similar between the DR and non-DR Group (p = 0.134 and p = 0.159 respectively). Analyses of the risk factors distribution between the study groups revealed that hypertension and dyslipidaemia demonstrated their significant presence in the DR-Group than those in the Non-DR Group (p = 0.05.0 and p = 0.008 respectively). ACR was observed to be inappreciably higher in the former group than that in the latter group (p < 0.001). Comparison of diabetes profile between the study groups shows that duration of DM, FPG and HbA1c were also significantly higher in the DR Group than those in the Non-DR Group (p < 0.001, p = 0.044 and p < 0.001 respectively). In terms of correlation, duration of DM and HbA1c were observed to be linearly correlated with MPV (r = 0.510, p < 0.001 and r = 0.571, p < 0.001 respectively) However, there was no significant difference between the study groups in terms of platelet count and MPV (p = 0.207 and p = 0.820 respectively). The risk of having larger MPV in diabetic patients with DR was 1.2-fold (95% CI = 0.45-3.27) higher than that in diabetic patients without DR (p = 0.701).Conclusion: The study concluded that there is no association of diabetic retinopathy with platelet count and MPV. The risk of having larger MPV in diabetic patients with DR is not significantly higher than that in diabetic patients without DR.Ibrahim Card Med J 2021; 11 (2): 47-55